2x+4x+6x-2(x+3)=34

Simple and best practice solution for 2x+4x+6x-2(x+3)=34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+4x+6x-2(x+3)=34 equation:


Simplifying
2x + 4x + 6x + -2(x + 3) = 34

Reorder the terms:
2x + 4x + 6x + -2(3 + x) = 34
2x + 4x + 6x + (3 * -2 + x * -2) = 34
2x + 4x + 6x + (-6 + -2x) = 34

Reorder the terms:
-6 + 2x + 4x + 6x + -2x = 34

Combine like terms: 2x + 4x = 6x
-6 + 6x + 6x + -2x = 34

Combine like terms: 6x + 6x = 12x
-6 + 12x + -2x = 34

Combine like terms: 12x + -2x = 10x
-6 + 10x = 34

Solving
-6 + 10x = 34

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 10x = 34 + 6

Combine like terms: -6 + 6 = 0
0 + 10x = 34 + 6
10x = 34 + 6

Combine like terms: 34 + 6 = 40
10x = 40

Divide each side by '10'.
x = 4

Simplifying
x = 4

See similar equations:

| 6(2j+1)+7= | | 8+4x=5x+4 | | -1+5(x+2)=12x+3-17x | | X+3x+2x+3(x+1)=30 | | 5-16=8.5 | | 3x-6y+9= | | 3(4+10x)+x= | | 8x+4x=5x+4 | | x^4-4x^3-x^2+16x=0 | | 2x-3(-5x+8)=17x-2+8 | | 5(a+4)-6a+1=12 | | -8(y+2)-16=16 | | -1+5(x+2)=12x+3-1x | | 3y^4-13y^2-10=0 | | 28+2x-1=3x+22 | | 19.5(13.3-4.4x)=7.2(0.8x-116) | | 4(5t+10)= | | t^4+21t^2+20=0 | | t^4+21lt^2+20=0 | | 6z-12= | | 4(3x-1P)=2(x+3) | | 4(a+2)-9=11 | | 3m-2=8 | | sqrt(3x)+1=x+1 | | t^4+2lt^2+20=0 | | -4(y+3)-2y=24 | | 2x^2+170=0 | | -9(x+3)+4x=-2 | | 11x^4+21x^3-35x^2-63x+6=0 | | 8(6n+10)+6n= | | 6(x+2)-4x+6=36 | | 5x^2-135x=0 |

Equations solver categories